Centro de interpretação do Pampa Jaguarão (RS): a revitalização de um patrimônio cultural - Bôas, Alexandre dos Santos Villas (2014)
This paper studies the cultural heritage revitalization of a building named Army Infirmary from Jaguarão, city, which will be the base for the Understanding Pampas Center construction, a complementary organ of the Universidade Federal do Pampa. The proposal is to contrast the building history from the architecture point of view, memory and analysis of the Understanding Pampas Center project and its impact on the local community. From this view, this paper intents to suggest alternatives to nullify the impact, through the community heritage education and supervisors, aiming to improve its usage and appropriation of the cultural complex.